2019
DOI: 10.5219/1143
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of analysis and the nutritional value of fresh common carp, frozen and southern canned tuna

Abstract: Freezing and canning are suitable methods to delay the spoilage of marine products and improve their physico-chemical and organoleptic properties. The fish were transported to the ice in proportion to 1 to 3 (w/w) inside the boxes, and then moved wastes. The purpose of this project is to analyse and to compare the nutritional value of fresh, frozen the fish and canned tuna fish. Nutrient composition and pH of the fresh fish fillet and moisture and ash contents and other nutrient composition were measured by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In the present study, this relationship was also observed. Aberoumand ( 2014 ) study showed that the percentage of protein in fresh yolk tuna fillet was lower than canned fish after 2 months of storage, but with over time, the percentage of protein in canned fish fillet decreased compared to the control. The fat percentage in canned fish was higher than in fresh samples.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, this relationship was also observed. Aberoumand ( 2014 ) study showed that the percentage of protein in fresh yolk tuna fillet was lower than canned fish after 2 months of storage, but with over time, the percentage of protein in canned fish fillet decreased compared to the control. The fat percentage in canned fish was higher than in fresh samples.…”
Section: Resultsmentioning
confidence: 99%
“…This method was based on processing of fish canning that fillet is heated during sterilization in autoclave. 7 The purpose of this step was to remove fat and water from fish fillet due to heat under pressure of water vapor, and then fish tissue became soft.…”
Section: Thawing In Hot Watermentioning
confidence: 99%